2023
DOI: 10.1155/2023/4980391
|View full text |Cite
|
Sign up to set email alerts
|

Health Information Technologies in a Resource‐Limited Setting: Knowledge, Attitude, and Practice of Health Professionals

Abstract: The use of health information technology significantly enhances patient outcomes. As a result, policymakers from developing countries have placed strong emphasis on formulating eHealth policies and initiatives. However, there have not been many successful deployments to show for. The role of individual factors in the successful implementation of these technologies is indispensable. Therefore, this study assesses healthcare professionals’ knowledge, attitudes, and practice of health information technology. An i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 28 publications
0
2
0
1
Order By: Relevance
“…"Self-regulation" in this context refers to a capacity to take care of oneself whereas simultaneously monitoring one's own behavior and, when confronted with difficult circumstances, finding ways to cope in an adaptive manner. According to (Daga et al) [14] our findings, the professional competency of teachers includes the following: in-depth prior conceptual knowledge, beliefs in constructivism, an inherent orientation toward their task, and the ability to self-regulate. (Indrayogi and Sofyan) [15] The results of empirical study have shown that the aforementioned instructor factors indicate greater comprehension of the educational environment and seem to create good impacts in pupils.…”
mentioning
confidence: 79%
“…"Self-regulation" in this context refers to a capacity to take care of oneself whereas simultaneously monitoring one's own behavior and, when confronted with difficult circumstances, finding ways to cope in an adaptive manner. According to (Daga et al) [14] our findings, the professional competency of teachers includes the following: in-depth prior conceptual knowledge, beliefs in constructivism, an inherent orientation toward their task, and the ability to self-regulate. (Indrayogi and Sofyan) [15] The results of empirical study have shown that the aforementioned instructor factors indicate greater comprehension of the educational environment and seem to create good impacts in pupils.…”
mentioning
confidence: 79%
“…3 El uso de algoritmos avanzados y el análisis de grandes datos permitirá a los profesionales de la salud tomar decisiones más precisas y mejorar los resultados clínicos. 4 El retraso en la integración de tecnologías digitales en la salud, en comparación con otros sectores, incluye varios factores: los altos costos y la complejidad de las tecnologías necesarias para la implementación de la transformación digital, brechas en la capacitación y la formación de los profesionales de la salud en el uso de estas tecnologías, lo que limita la adopción de soluciones digitales 5 ; y las barreras culturales así como la resistencia al cambio dentro de las organizaciones de atención médica.…”
Section: El Sector Salud En La Era De Launclassified
“…However, these incredible advances have not been matched by the human element. Many healthcare professionals have not received any training in using information communication technologies (ICT) in the professional environment 1 and belong to the population known as digital immigrants. 2 Healthcare professionals also encounter many legislative, instrumental or even ethical limitations when applying ICT to their daily practice with their patients.…”
Section: Introductionmentioning
confidence: 99%